Desarrollo de Protocolos de Evaluación del Bienestar Animal en la Cadena de la Carne Bovina: Sistemas de Recría y Determinación Extensivo y Semi-Intensivo. CVT INTA – IPCVA 28.442. Primer Informe Parcial, Período abarcado: abril de 2022 – marzo de 2023. - Langman, Leandro Ezequiel; Cancino, Andrea Karina; Pighin, Darío Gabriel; Racciatti, Débora; Bottegal, Diego Nicolas; Gallard, Eliana Andrea; Marcoppido, Gisela Ariana; Leiton, Héctor Rafael; Bain, Ingrid; Blanco Penedo, Isabel; Fernández Madero, Julieta; Menichelli, Marcela Liliana; et al. (CVT INTA – IPCVA, 2025)
With the growth of the world's population, the need to reduce losses in the quantity and quality of livestock products has led to a growing interest and need to consider the welfare of farm animals. Additionally, there is a growing consumer demand for the "ethical quality" of the products they consume. This latter concept encompasses all actions aimed at minimizing animal suffering at the various stages of the livestock supply chain. Considering this topic falls within the concept of "One Well-being," which recognizes the relationship between animal welfare, human well-being, and environmental stewardship, providing a framework for fostering interdisciplinary collaboration with the goal of improving these aspects globally. Many aspects need to be improved through the application of validated scientific information generated in the context of each country and region. In this context, meat-producing countries must not only provide good quality and safe meat to their respective countries and the world, but also have and project a sustainable and animal welfare-friendly image (del Campo et al., 2014). Like many other countries, Argentina needs its own information on this topic, and the National Institute of Agricultural Technology can significantly contribute to generating the necessary knowledge as a tool for assessing the degree to which production facilities promote animal welfare. Currently, the tools used to assess the condition of animals in rearing, extensive, and semi-intensive production systems are either nonexistent or diversified, relying on methodologies developed in other countries or for other production systems, using indicators that are not always applicable in the target production systems. Based on this, obtaining developed animal welfare assessment protocols would provide the input for conducting a situational analysis that considers animal welfare principles in specific scenarios, enabling the identification of critical points and specific corrective actions at the various stages of the production chain. The overall objective of this project is to develop animal welfare assessment protocols at the field level for cattle intended for beef production, in the aforementioned finishing systems, as well as at the rearing level.